Currency Demand Forecasting For Automated Teller Machines (ATMs) Of Banks - Doss, Paul (2010)
This research aims to determine if the use of an efficient ATM Cash Forecasting Tool (ATM CFT) would actually help improve the cash utilization of ATMs. The ATM Cash Utilization rate is measured prior to the use of an ATM CFT. The ATM CFT is then used to forecast what appropritae amounts of cash should have been loaded into the ATMs for the same period and the new ATM Cash Utilization rate is then measured. The findings reveal that ATM CFT does significantly improve ATM Cash Utilization Rates.